SOCIOEMOTIONAL SKILLS AND THEIR IMPLICATIONS IN THE EDUCATIONAL CONTEXT - Sobral Pereira, Juscelino (Revista Gênero e Interdisciplinaridade, 2023)
The socioemotional educational approach not only focuses on understanding and managing emotions, thoughts, and behaviors, but also on building healthy and effective relationships. It also goes beyond the development of specific socioemotional skills, such as self-confidence, resilience, empathy, and coping with difficult situations, and encompasses other relevant skills. Rather than describing the socioemotional educational approach in a restrictive manner, it is important to have a broad and comprehensive view that includes a wide range of skills and important aspects for emotional and social development. The aim of this study was to discuss the importance of socioemotional skills in the educational context, exploring how they can be developed and examining how the inclusion of these skills can contribute to a more balanced and healthy learning environment. The research method used in this study was based on books, scientific articles from scientific databases such as Medline, Lilacs and SciELO, and internet articles, therefore this is bibliographical research. After reading, analyzing, comparing, and synthesizing the content of scientific articles from different authors regarding the subject at hand, it was found that socioemotional skills are effective in enhancing the teaching and learning process.